Friction Influenced by Vibrations: A Refined Contact-Mechanics View on Lateral and Rotational Oscillations - Pohrt, Roman (Frontiers in Mechanical Engineering, 2020)
It is known that superposed movements can lower the friction felt at the macroscale. This is well documented for in-plane and normal translatory oscillations. Contact mechanics are a suitable approach to model this effect but so far have not gone beyond single-slider dynamics. In this study, we make use of 3D Boundary Elements Simulations to study the macroscopic friction reduction. This approach allows us to take into account also partial sliding of the contact zone. We first revisit the case of transversal in-plane translatory oscillations. Here, we argue that the behavior at small velocities can best be described when partial slip is indeed taken into account. Next, we investigate the frictional response of a Hertzian indenter when the lateral movement is superposed with a rotational bore movement. An analytical approximation is given for the steady state solution with constant angular velocity. The third case under investigation is an oscillating bore rotation. We present numerical results for the reduction of the macroscopic friction. In two limiting cases, an analytical prediction is given, following the lines used in the translatory case. For extremely large amplitudes, it is based on the idea that a rotational steady state is assumed at every instant. For small velocities we adapt our new approach including partial sliding. We find these predictions to be good but not perfect, slightly underestimating the reduction that rotational oscillations can provide.